Optimal CSP-1 boundary scheme based on the estimator of the proportion of conformance for specified in-control process. Issue 1 (2nd January 2020) - Li, Chunzhi; Tong, Shurong; Wang, Keqin; Zhang, Xinwei
ABSTRACT: Single-level continuous sampling plan (CSP-1), called A O Q L contour scheme, is constructed on the average outgoing quality limit ( A O Q L ) contour. However, for specified in-control process the boundary of feasible continuous sampling scheme is not established in CSP-1. The optimal CSP-1 boundary scheme is established based on the estimator of the proportion of conformance for specified in-control process. The parameters of the boundary scheme are determined by the set of equations constructed with the boundary identical equation and contour identical equation, which will guarantee that the proposed scheme is simultaneously both boundary scheme and contour scheme. The behaviour of the established boundary scheme is discussed and compared with the A O Q L contour scheme. The optimal CSP-1 boundary scheme can quantitatively control the outgoing quality and tighten the inspection whether the process quality fluctuates towards the deteriorated or the improved direction. For practitioners' convenience, three tables of the boundary scheme parameters under three quality requirements and three confidence levels are provided. The operating procedure is also presented. A real example is given to verify the effectiveness and feasibility of the proposed boundary scheme.